Effects of viscous dissipation and thermal radiation on MHD forced convective heat and mass transfer flow of non-Newtonian power law fluid with heat generation - Samad, MA; Podder, C (Bangladesh Journal of Scientific Research, 2016)
An analysis is carried out to investigate the effects of forced convection heat and mass transfer of an electrically conducting, non-Newtonian power-law fluid past a stretching sheet. This has been done under the simultaneous action of suction, radiation, uniform transverse magnetic field, heat generation and viscous dissipation. The stretching sheet is assumed to continuously moving with a power-law velocity and maintaining a uniform surface heat flux. The governing nonlinear partial differential equations are transformed into a system of nonlinear ordinary differential equations using appropriate similarity transfor-mations. The resulting dimensionless equations are solved numerically using sixth order Runge-Kutta integration scheme with Nachtsheim-Swigert shooting iterative technique. A systematical study of numerical results for the non-dimensional velocity, temperature and concentration profiles are presented graphically. Due to physical and engineering interest, the viscous drag or local Skin-friction coefficient, heat transfer rate or local Nusselt number and mass transfer rate or local Sherwood number are represented in tabular form to illustrate the details of flow characteristics and their dependence on all physically important parameters of different non-Newtonian fluids. A comparison of the present study and previously published paper has also been shown in tabular form. Bangladesh J. Sci. Res. 27(2): 187-200, December-2014